FLOFLOFLO : The Ultimate Faucet / Nur Shukrina Aida Mustapa - Mustapa, Nur Shukrina Aida (2020)
FLOFLOFLO is a faucet specialist company that is determined to provide ideal cleanliness for daily usage. At first, we start our business by providing a sensor automated faucet comes with soap application. This innovative idea comes from the pandemic that occur in Malaysia leads to giving better hygiene services for this country. The competitive advantage that we have is that, our product has dual-sensor used for water and soap output based on preferences. The management team consists of 5 members which include the director, vice director, financial manager, operational manager and marketing manager. With the experts present in the company had provided the specialty this will ensure that our product meets the standard quality in order to satisfy the customer’s expectations. The sales forecast is calculated based on Ringgit Malaysia in some period of time. For our business, the sales projection is calculated every month referred to the customer awareness of our business, preferences and other factors. Besides, we targeted the sales forecast for the year 2022 is RM 184, 527, 360 and increasing by 25% for the next year and 30% in the following year. Our future expectation is that FLOFLOFLO will be able to evolve and offer a wider range of quality products that would satisfy the customer needs and can expand from a mini production to the factory. We will strive to become one of the best company in Malaysia and able to expand our business in the local market.